2023
DOI: 10.1097/prs.0000000000010800
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Migraine Headache Index versus Monthly Migraine Days after Headache Surgery: A Systematic Review and Meta-Analysis

Abstract: Volume 153, Number 6 • MHI versus MMD after Nerve Deactivation a Only studies reporting complications were included in the analysis. A total of 401 patients were included among the studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Neurologists are the specialists traditionally and most often tasked with treating headache patients and working to understand how they define, speak about, and treat headaches will continue to be beneficial to both specialties andmost importantly, to patients. 52 , 53 This type of partnership, in turn, fosters a better understanding of what we as surgeons can offer such patients and provides a presence in the neurology literature 54 backed not only by data in the plastic surgery pantheon, but by other viewpoints on the anatomy and physiology of chronic headaches that challenge long held norms. 55 , 56 This type of teamwork will open up surgical treatment to many patients in the future, likely as part of a multimodality approach to their condition.…”
Section: Headache Surgery: 2023 and Beyond – 5 Developments Shaping T...mentioning
confidence: 92%
“…Neurologists are the specialists traditionally and most often tasked with treating headache patients and working to understand how they define, speak about, and treat headaches will continue to be beneficial to both specialties andmost importantly, to patients. 52 , 53 This type of partnership, in turn, fosters a better understanding of what we as surgeons can offer such patients and provides a presence in the neurology literature 54 backed not only by data in the plastic surgery pantheon, but by other viewpoints on the anatomy and physiology of chronic headaches that challenge long held norms. 55 , 56 This type of teamwork will open up surgical treatment to many patients in the future, likely as part of a multimodality approach to their condition.…”
Section: Headache Surgery: 2023 and Beyond – 5 Developments Shaping T...mentioning
confidence: 92%
“…Since Guyuron’s initial description, 1 numerous studies have been carried out around the world, unequivocally demonstrating the validity of this approach. 2–24 This approach is based on the neurolysis of extracranial nerves, which, when inflamed, act as trigger points and, as such, trigger headache attacks. Two of the nerves most frequently involved are the greater occipital nerve (GON) and lesser occipital nerve (LON).…”
Section: Techniquementioning
confidence: 99%
“…15 This surgical intervention has demonstrated noteworthy success, as multiple studies have demonstrated the safety and efficacy of migraine surgery. 16–21 Although the success of this procedure has been demonstrated, it is unclear whether advancements in migraine treatment are known to the general public. 22…”
Section: Introductionmentioning
confidence: 99%
“…15 This surgical intervention has demonstrated noteworthy success, as multiple studies have demonstrated the safety and efficacy of migraine surgery. [16][17][18][19][20][21] Although the success of this procedure has been demonstrated, it is unclear whether advancements in migraine treatment are known to the general public. 22 In contrast to the targeted marketing and visibility enjoyed by pharmaceutical innovations like Nurtec, surgical interventions for migraines, such as nerve release surgery, often remain overshadowed in public awareness.…”
Section: Introductionmentioning
confidence: 99%